2021
DOI: 10.1016/j.jad.2020.11.065
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between post-traumatic stress and positive mental health symptoms among health workers during COVID-19 pandemic in Lombardy, Italy

Abstract: Background: The COVID-19 pandemic is exposing health workers (HW) worldwide to extreme burden and risk of developing post-traumatic stress disorder (PTSD). This problem emerged in Lombardy, the Italian region where the pandemic exacted the heaviest toll. Study aims were to assess mental health of HW in Lombardy after the peak of COVID-19 related hospitalizations, through the joint evaluation of PTSD and positive mental health; and to explore the potential role of positive mental health in PTSD development. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
64
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 29 publications
16
64
2
6
Order By: Relevance
“…No gender and working characteristic' differences were found, contrary to current literature describing differences for frontline nurses in terms of well-being, feelings of burn-out, fear of self-infection, and of their performance and quality of care for the patients [14,24,32,44,45]. Due to the significant increase in working hours and number of COVID-19 patients who need to be assisted, the stressful clinical practice of frontline healthcare workers could have determined frustration, feelings of lower competence, and low-self-esteem directly related to the growing number of deaths during the current pandemic.…”
Section: Discussioncontrasting
confidence: 66%
“…No gender and working characteristic' differences were found, contrary to current literature describing differences for frontline nurses in terms of well-being, feelings of burn-out, fear of self-infection, and of their performance and quality of care for the patients [14,24,32,44,45]. Due to the significant increase in working hours and number of COVID-19 patients who need to be assisted, the stressful clinical practice of frontline healthcare workers could have determined frustration, feelings of lower competence, and low-self-esteem directly related to the growing number of deaths during the current pandemic.…”
Section: Discussioncontrasting
confidence: 66%
“…Dentro de un estudio realizado en profesionales de salud en España, Turquía, Serbia, Estados Unidos, Rumanía, Italia y Reino Unido, se determinó que el grupo más afectado durante la pandemia fueron los que se encontraban en primera línea frente a la COVID 19, en especial, las enfermeras, que se caracterizaban por padecer estrés, ansiedad, Síndrome de Burnout, depresión y alteración del sueño (insomnio), más que otros profesionales de salud. Se encontró de igual manera El hecho de que el personal sanitario sea responsable del cuidado de pacientes con COVID-19 sin contar con el tratamiento específico ni apoyo adecuado, y asimismo se encuentre expuesto a situaciones médicas críticas y la muerte, hace que sea especialmente vulnerable al trastorno de estrés postraumático 31,32 .…”
Section: Discussionunclassified
“…During trying times, a number of factors can help individuals survive, manage and adapt. Bassi et al ( 2021 ) found that Italian health workers classified as thriving individuals were less likely to have post-traumatic stress (PTSD) during the pandemic. The term thriving denotes the state of fully functioning in mental, physical, and social terms (Su et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%